2017
DOI: 10.21276/ap.2017.6.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Application of amylase producing bacteria isolated from hot spring water in food industry

Abstract: Due to the increasing demand for enzymes in various industries, there is enormous interest in research on enzymes suitable for commercial applications and their cost effective production techniques. Thermophilic microorganisms have gained a great deal of attention. Hence, the enzyme from these microorganisms is of special interest because these are not usually denatured by high temperature and are active at elevated temperature. The amylase from thermophilic bacteria of hot springs which are supposed to be une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…α‐amylase produced by a thermophilic Bacillus sp. isolated from an Indian hot spring was used for kiwi and apple juice clarification and bun making (Rana, Verma, Vaidya, & Ghabru, 2017). The authors found that 1.25% (w/v) addition of α‐amylase during kiwi juice processing led to increased yield and best taste, color, flavor, and overall acceptability.…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…α‐amylase produced by a thermophilic Bacillus sp. isolated from an Indian hot spring was used for kiwi and apple juice clarification and bun making (Rana, Verma, Vaidya, & Ghabru, 2017). The authors found that 1.25% (w/v) addition of α‐amylase during kiwi juice processing led to increased yield and best taste, color, flavor, and overall acceptability.…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
“…For bun making, α‐amylase was added before mixing ingredients (wheat flour, sugar, yeast, and oil). The authors reported a maximum leavening activity of 2.60 ml/hr at an enzyme concentration of 0.75%, which considerably improved the quality of buns (Rana et al., 2017).…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
“…This is often supplied by the addition of malt or commercial preparations of fungal or bacterial α-amylase [10]. However, if an excess enzyme is present, starch is broken down to dextrins and simple sugars, resulting in a sticky, hard-to-handle dough that produces bread with a wet, sticky crumb [11].…”
Section: Introductionmentioning
confidence: 99%
“…The industrial application of enzymes is also hampered due to lack of reusability, availability and limited stability under operational conditions. In food industries, amylase enzymes are utilized in baking, brewing, preparation of digestive aids, preparation of cakes, fruit juices and starch syrups (Rana et al, 2017). The use of enzymes in a free form is very uneconomical because the enzymes generally cannot be recovered at the end of the reaction.…”
Section: Introductionmentioning
confidence: 99%